French bean seed production process - Ngo, Thi Hanh; Nguyen, Thi Lien Huong; Nguyen, Xuan Diep; Hoang, Minh Chau; Nguyen, Thi Phuong; Van, Lam Luong; Nabuuma, Deborah Sandra; Stomph, TjeerdJan; Swaans, Cornelis (2023)
The video documents the key steps in the production of French bean seed for farmers in Northern Vietnam. The training activities and this video were developed within the framework of the project “Integrated vegetable seed systems development in ethnic minority communities in Northern Vietnam for enhanced nutrition and income security”. A project part of the Netherlands - CGIAR Research Programme, funded by the Dutch Research Council (NWO). The video was also developed with support from the CGIAR Initiative on Nature-Positive Solutions for Shifting Agrifood Systems to More Resilient and Sustainable Pathways (NATURE+).